DESCRIPTION OF STUDENT’S JUNIOR HIGH SCHOOL MATHEMATICAL CONNECTION ABILITY ON THE LINEAR FUNCTION TOPIC - Aulia Suci Wardina; Eyus Sudihartinih (LP4MK STKIP PGRI Lubuklinggau, 2019)
This research aims to determine the mathematical connection ability of junior high school students in Bandung. This research uses descriptive qualitative method with data triangulation. The instrument used in the form is test description as many as three questions that have been consulted with experts and refers to indicators of mathematical connection ability. The results of this research describe 1) the ability of students to connect between mathematical concepts with a percentage of 58.33%, 2) the ability of students to connect and apply mathematical concepts in other disciplines of sciences with a percentage of 50%, 3) the ability of students to apply mathematical concepts to solving problems in daily life with a percentage of 66.67%. The results showed that the mathematical connection ability of junior high school students in Bandung on the topic of linear function was good enough.